ReefGuard Karimunjawa: A Role-Playing Board Game for Social–Ecological Conservation Education for Ages 16–18 - Chika Aprilia Damarani (Institut Seni Indonesia Yogyakarta, 2026)
This design research developed a prototype educational board game, ReefGuard: Karimunjawa, as an analog learning medium for social-ecological conservation in Karimunjawa National Park for adolescents aged 16–18. The game is a cooperative role-playing experience in which players take stakeholder roles, make team decisions, and observe consequences through shared social and ecological condition indicators. A pre-user test and post-user test with a playtest involving five respondents (N=5) evaluated gameplay mechanisms and visual–UI aspects. Results indicate positive acceptance: respondents understood the objectives and basic rules, found the icons easy to interpret, and rated the visual–UI highly (mean 4.7/5). They also reported increased conservation insights and improved understanding of human–nature relationships after playing. Nevertheless, several abstract mechanics require streamlined rules, stronger player aids, and a clearer information hierarchy to stabilize gameplay and strengthen the perceived meaningfulness of decisions.